2014
DOI: 10.1002/bjs.9331
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of plasma biomarkers in patients with acute intestinal ischaemia

Abstract: Serum biomarkers may be useful in the diagnosis of vascular, but not non-vascular, intestinal ischaemia. Among them, I-FABP shows promise for detecting vascular ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 31 publications
8
59
0
3
Order By: Relevance
“…22 Sensitivity and specificity for elevated levels of SGOT were 68% and 80% respectively in present study whereas other studies reported higher sensitivity of 70% to 80% and same specificity of 80%-90% for elevated serum SGOT in bowel ischemia patients. 20,23 They reported serum level of >100 U significant for bowel ischemia in the comparison of non-bowel ischemic patients which was similar to our study findings, in which we found SGOT levels >100 U significantly (p value <0.0001) related to bowel ischemia patients. 20 In present study for elevated levels of alkaline phosphates sensitivity and specificity were 72% and 68% respectively whereas others reported similar sensitivity of up to 70% to 80% but slight higher specificity of 70% to 80% in their study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…22 Sensitivity and specificity for elevated levels of SGOT were 68% and 80% respectively in present study whereas other studies reported higher sensitivity of 70% to 80% and same specificity of 80%-90% for elevated serum SGOT in bowel ischemia patients. 20,23 They reported serum level of >100 U significant for bowel ischemia in the comparison of non-bowel ischemic patients which was similar to our study findings, in which we found SGOT levels >100 U significantly (p value <0.0001) related to bowel ischemia patients. 20 In present study for elevated levels of alkaline phosphates sensitivity and specificity were 72% and 68% respectively whereas others reported similar sensitivity of up to 70% to 80% but slight higher specificity of 70% to 80% in their study.…”
Section: Discussionsupporting
confidence: 91%
“…20,23 They reported serum level of >100 U significant for bowel ischemia in the comparison of non-bowel ischemic patients which was similar to our study findings, in which we found SGOT levels >100 U significantly (p value <0.0001) related to bowel ischemia patients. 20 In present study for elevated levels of alkaline phosphates sensitivity and specificity were 72% and 68% respectively whereas others reported similar sensitivity of up to 70% to 80% but slight higher specificity of 70% to 80% in their study. 10,24,25 They stated level >140 U was specific for bowel ischemia, which was found to be similar to present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A vékonybél ischaemiás toleranciája 6 óra, ezt követően irreverzibilisen károsodik, ezért a korai diagnózis létfon-tosságú. Néhány humán vizsgálat során sikerült igazolni, hogy a szérum-I-FABP szintje megemelkedik az arteria mesenterica superior occlusiója esetén [8,15,[18][19][20][21]. Egy patkányokat használó kísérletes modellben az SE I. Sebészeti Klinika munkacsoportja kimutatta, hogy a szé-rum-I-FABP szintjének emelkedése jól korrelál a szövet-tani minták elemzése során talált intestinalis epithelsejtkárosodás mértékével [22].…”
Section: Nekrotizáló Enterocolitis Akut Mesenterialis Ischaemiaunclassified
“…Elevated amylase has been reported in roughly a half of patients with AMI [29]. Other biomarkers reported to assist in the diagnosis of AMI include intestinal fatty acid binding protein (I-FABP), serum alpha-glutathione S-transferase (alpha-GST), and cobalt-albumin binding assay (CABA) [30,31]. These biomarkers may offer improved diagnostic accuracy of acute mesenteric ischemia, however, further research is required to specify its accuracy and values.…”
Section: (Recommendation 1b)mentioning
confidence: 99%